Lecturers’ Perceptions on the Benefits and Challenges of English as a Medium of Instructions (EMI) Program: North Bali Context - Sudana, Putu Ayu Prabawati; Ratminingsih, Ni Made; Padmadewi, Ni Nyoman; Adnyani, Ni Luh Putu Sri (English Department FBS UNP, 2023)
EMI program is an innovative program that has gained high popularity in the countries where English is a second or foreign language. This is due to the benefits that the program offers; to the students, the lecturers and the institutions. However, the program also brings up some challenges that have to be settled by all that involve. This study investigates the lecturers’ perception on the benefits and challenges of EMI Program in a public university in North Bali, Indonesia. The data were collected by distributing questionnaires to the lecturers who taught in EMI classes. Data triangulation was conducted by doing a semi-structured interview with three lecturers. The study findings revealed that the most of the lecturers agreed on the benefits of EMI classes in increasing the exposures of the lecturers and students to English and opportunity in using it and improving the English skills of both the lecturers and students, as well as the students’ content learning. Regarding the institutions’ profile and internationalization, most of the lecturers agreed that EMI classes give contribution to them. In addition, most of the lecturers also perceived that EMI classes increase the lecturers’ and students’ career and study prospect. In terms of the challenges of the EMI program, most of the lecturers mostly agreed that the lecturers’ and students’ language abilities, students’ participation, EMI pedagogy, which includes the effective teaching strategies were challenges that they faced in the program implementation. However, regarding learning resources and technology used in EMI classes, most of them disagreed with the statements; meaning that they did not encounter difficulty in accessing resources and integrating the needed technology in their EMI classes